Understanding pathways for effective interprofessional education: a thematic analysis of medical and nursing students’ insights - Amal Jasim Al-Qallaf; Muhammad Umair Akhtar; Mohamed Nagi Fouda; Omar Anwar Alyas; Jannat Akram; Rahaf Mashal; Nashmiyya Atif (BMC Medical Education)
Abstract Background As the healthcare field is undergoing a paradigm shift, the role of interprofessional education (IPE) is being widely accepted and recognized. Despite this, IPE interventions are not employed globally and the use of such interventions is variable. Additionally, there is an ongoing debate over how and when to employ IPE interventions. This qualitative study was conducted at Royal College of Surgeons in Ireland – Bahrain (RCSI Bahrain) to understand medical and nursing students’ attitudes, expectations, perspectives and experiences in relation to IPE. Methods Medical and nursing students from all cycles and levels of the medical and nursing programs at RCSI Bahrain participated in Focus Group Discussions (FGDs) and interviews where they discussed issues and opinions related to IPE. These discussions were then transcribed for analysis. Thematic analysis of the data using a grounded theory approach was carried out using a four-staged process of reading transcripts, identifying possible themes and structures and building theory. Results 16 elected class representatives participated in the study. The comprehensive process of thematic analysis led to the emergence of five themes and associated subthemes: integrated curriculum (realistic interventions, idealistic interventions, varied perspectives), role recognition (communication, task division), understanding of team dynamics (harmonious collaboration, amplification of strengths, team management), cultural practices (organizational culture, interpersonal culture), and social conditioning (identity navigation, stereotype persistence, varied mindsets). The sequential relationship between these themes provides an approach for integrated IPE in healthcare curricula. Conclusion This qualitative study investigated medical and nursing students’ perspectives on IPE at RCSI Bahrain. The identified themes provide a valuable framework for policymakers and medical educators to design and implement effective IPE interventions, thereby enhancing interprofessional collaboration and improving patient outcomes in healthcare settings.